2008
DOI: 10.1088/1009-0630/10/6/09
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Thermal Efficiency of a Non-transferred DC Plasma Spraying Torch Under Low Pressure

Abstract: Current-voltage (I-V ) characteristics of a non-transferred DC arc plasma spray torch operated in argon at vacuum are reported. The arc voltage is of negative characteristics for a current below 200 A, flat for a current between 200 A to 250 A and positive for a current beyond 250 A. The voltage increases slowly with the increase in carrier gas of arc. The rate of change in voltage with currents is about 3∼4 V/100 A at a gas flow rate of about 1∼1.5 V/10 standard liter per minute (slpm). The I-V characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
2
2
2
Order By: Relevance
“…Typically, for a current below 150 A the V -I characteristic shows a negative slope, which then turns positive beyond a plasma current of 200 A, a trend also noticed in previous studies [16] . The corresponding range of the plasma current as reported by BAO Shicong et al [16] is slightly higher than our results. They got a negative slope below a current of 200 A and a positive slope above 250 A.…”
Section: Effect Of Plasma Current On V -I Characteristicsupporting
confidence: 84%
See 3 more Smart Citations
“…Typically, for a current below 150 A the V -I characteristic shows a negative slope, which then turns positive beyond a plasma current of 200 A, a trend also noticed in previous studies [16] . The corresponding range of the plasma current as reported by BAO Shicong et al [16] is slightly higher than our results. They got a negative slope below a current of 200 A and a positive slope above 250 A.…”
Section: Effect Of Plasma Current On V -I Characteristicsupporting
confidence: 84%
“…The measured efficiency of the plasma torch is found to be in the range from 36% to 48%, for different gas flow rates and currents, which always increases with the gas flow rate and arc power, for a constant current. However, the efficiency reported for thermal plasma spraying torches [14,16] is higher than our measured values. BAO Shicong et al [16] reported on achieving an efficiency in the range of 65% and 78%, with an almost similar trend.…”
Section: Heat Deposition Profile Of DC Plasma Torch and Estimation Of...contrasting
confidence: 83%
See 2 more Smart Citations
“…It is known that the plasma power increases with the increase in gas flow rate [15,19,20] . Also, the particle velocity increases with the gas flow rate.…”
Section: Effect Of Plasma Gas Flow Rate On the Properties Of Alumina-...mentioning
confidence: 99%